Employee selection, education, and firm-provided training - Marco Barrenechea-Méndez; Pedro Ortín Ángel; Eduardo C. Rodes-Mayor (BRQ Business Research Quarterly, 2022)
Theoretical debate suggests at least three strategies for firms to provide training to employees in the same job position: individualized and egalitarian with or without adaptation to the abilities of the recruited employees. The article provides a formal framework for deriving distinctive empirical implications regarding the relationship of these strategies with the firms' selection policies, which are tested using a dataset of blue-collar workers in Spanish industrial plants. The evidence is consistent with the empirical implications of the egalitarian strategy with adaptation. This strategy entails providing the same level of training to all workers in the same job position and setting this level according to the average ability of recruited workers. Paradoxically, this strategy has not been used to interpret the results of the existing empirical literature.
Keywords: M53; M54; M21; J24; 650; selection and education; Training